2002
DOI: 10.1021/jf020195p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pig Slurry Application on Soils and Soil Humic Acids

Abstract: The effect of three annually consecutive additions of pig slurry at two rates (90 and 150 m3 x ha(-1) x year(-1) on soils and soil humic acids (HAs) was investigated in a field experiment under semiarid conditions. Soils and pig slurries were analyzed by standard methods. The HAs were isolated from soils and pig slurry by a conventional procedure based on alkaline extraction, acidic precipitation to pH 1, purification by repeated alkaline dissolutions and acidic precipitations, water washing, dialysis, and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
48
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 29 publications
13
48
0
Order By: Relevance
“…As a whole, the results of elemental, functional, FT IR, fluorescence, ESR and NMR analyses described above together with additional evidence provided by other authors [29,40,[86][87][88][89] indicate that, with respect to soil HA and FA, HA-and FA-like fractions isolated from LSM and other animal manures are rich in incompletely humified materials characterized by a prevalent aliphatic character, small acidic oxygenated functional group content, small polycondensation and polymerization degree, and larger presence of polysaccharide and S-and N-containing groups, most probably proteinaceous materials. yr -1 of LSM over a seven-year period, were investigated by use of a current potentiometric titration method and fitting the NICADonnan model to titration data [90].…”
Section: Animal Manuresmentioning
confidence: 53%
“…As a whole, the results of elemental, functional, FT IR, fluorescence, ESR and NMR analyses described above together with additional evidence provided by other authors [29,40,[86][87][88][89] indicate that, with respect to soil HA and FA, HA-and FA-like fractions isolated from LSM and other animal manures are rich in incompletely humified materials characterized by a prevalent aliphatic character, small acidic oxygenated functional group content, small polycondensation and polymerization degree, and larger presence of polysaccharide and S-and N-containing groups, most probably proteinaceous materials. yr -1 of LSM over a seven-year period, were investigated by use of a current potentiometric titration method and fitting the NICADonnan model to titration data [90].…”
Section: Animal Manuresmentioning
confidence: 53%
“…It has also been suggested that adding slurry to the soil enhances mineralization as a priming effect and that this is larger in soils with higher C and N (Kuzyakov et al 2000;Plaza et al 2002). Application of pig slurry resulted in DM yields of silage maize that were almost similar to those receiving mineral N. This is astonishing as the NH 4 proportion in pig slurry was 75% of total N. The effect of cattle slurry was smaller but still stronger than expected (Sommer and Hutchings 2001).…”
Section: Apparent N Recoverymentioning
confidence: 91%
“…With increasing amendment rate and number, free radical concentrations of amended soil HAs and FAs decrease with respect to those of the corresponding unamended soil HAs and FAs (Plaza et al, 2002(Plaza et al, , 2003Gonz á lez -P é rez et al, 2006 ). The concentration of organic free radicals in HS is generally related positively to the aromatic polycondensation, polymerization, and humifi cation degree and may infl uence (a) their reactivity with metal ions and organic chemicals and (b) their physiological activity (Steelink, 1987 ;Senesi and Steelink, 1989 ;Senesi, 1990aSenesi, ,b , 1996Cheshire and Senesi, 1998 ).…”
Section: Electron Spin Resonance Spectramentioning
confidence: 90%
“…The free radical concentrations of HAs and FAs from organic amendments are generally much smaller than those of native soil HAs and FAs (Figure 4.10 ) (Hervas et al, 1989 ;Jerzykiewicz et al, 1999 ;Plaza et al, 2002Plaza et al, , 2003SolerRovira et al, 2002SolerRovira et al, , 2003Gonz á lez -P é rez et al, 2006 ). With increasing amendment rate and number, free radical concentrations of amended soil HAs and FAs decrease with respect to those of the corresponding unamended soil HAs and FAs (Plaza et al, 2002(Plaza et al, , 2003Gonz á lez -P é rez et al, 2006 ).…”
Section: Electron Spin Resonance Spectramentioning
confidence: 95%
See 1 more Smart Citation